Isolation and Characterization of Infection of Four New Bacteriophages Infecting a Vibrio parahaemolyticus Strain - João Duarte; David Trindade; Vanessa Oliveira; Newton C. M. Gomes; Ricardo Calado; Carla Pereira; Adelaide Almeida (MDPI AG, 2024)
Bacteria from genus Vibrio continue to be one of the most common threats to aquaculture sustainability. Vibrio spp. have been associated with infectious outbreaks in fish, shrimp, bivalves and even algae farms worldwide. Moreover, several Vibrio spp. are also pathogens that impact human health and are a threat to public health when transferred to consumers through contaminated seafood products. The use of bacteriophages is an evolving technology that could be applied in the treatment of Vibrio spp. either to protect aquaculture farms or to decontaminate seafood, namely bivalves during their depuration. In the present study, bacteriophages vB_VpS_LMAVpS1 (S1) vB_VpS_LMAVpVPP (VPP), vB_VpS_LMAVpSH (SH) and vB_VpS_LMAVpH (H) infecting V. parahaemolyticus were isolated and characterized. All phages presented fast adsorption rates and were able to control V. parahaemolyticus at all multiplicity of infections (MOIs) tested (MOI of 1, 10 and 100), with reductions of more than 4 log CFU/mL being recorded, but only in the presence of divalent cation calcium. The rate of emergence of phage-resistant mutants was very low (1.8 × 10−6 to 3.1 × 10−6). Bacterial phage resistance was not permanent and led to a loss of bacterial fitness. All four phages presented with lysins encoded in their genomes. The results presented provide valuable insights for future studies in the application of these bacteriophages in different scenarios to control, decontaminate or treat bacterial infections or contaminations of V. parahaemolyticus.